ELISA‐type assays of trace biomarkers using microfluidic methods. (20th February 2017) - Dong, Jinhua; Ueda, Hiroshi
Abstract : Recently, great progress has been achieved for analytical technologies for biological substances. Traditionally, detection methods for analytes mainly rely on large instrumental analyses. These methods require costly equipment, skilled operators and long measurement time despite their generally low sensitivity. In contrast, immunoassays are becoming more and more popular for it is powerful, inexpensive, and convenient nature. Immunoassay has a range of applications, because it employs antibody, a protein produced by plasma cells in the acquired immune system to identify and neutralize diverse pathogens and other exogenous substances. However, the sensitivity of conventional immunoassays so far is limited by their reaction principles and detection methods. The microfluidics technology is the one that manipulates small volumes of fluid and flow, which has the potential to miniaturize many laboratory procedures. Immunoassays on microfluidic devices have been studied extensively and have gained significant attention owing to intrinsic advantages offered by the assay platforms. The techniques have allowed the miniaturization of conventional immunoassay and bring the advantages such as small volumes of samples and reagents as well as the decrease of contamination, which results in the decline of false‐positive results. Ultimately, the combination of immunoassays with microfluidics affords a promising platform for multiple, sensitive, and automatic point‐of‐care diagnostics. Recent achievements on microfluidic devices and immunoassay detection systems including digital assay employing single molecule will be introduced in detail and the strategies for faster and more sensitive configurations in microfluidic immunosensors will be highlighted. WIREs Nanomed Nanobiotechnol 2017, 9:e1457. doi: 10.1002/wnan.1457 This article is categorized under: Diagnostic Tools > Biosensing Diagnostic Tools > Diagnostic Nanodevices Abstract : Micro open‐sandwich enzyme‐linked immunosorbent assay.